Kepemimpinan Partisipatif Dan Iklim Kerja Terhadap Kepuasan Kerja Karyawan Pada Lembaga Jaminan Sosial Ketenagakerjaan - M. Afdalah Habibi; Nina Nurani (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2026)
This study aims to analyze the influence of participative leadership and work climate, both partially and simultaneously, on employee job satisfaction. The study was conducted at the Directorate of Strategic Planning and Information Technology of the National Workforce Social Security Authority headquartered in Jakarta, Indonesia, employing a quantitative explanatory approach. Using the Slovin formula applied to a population of 194 non-managerial permanent employees, the sample consisted of 66 respondents selected through purposive sampling. Data were collected using a validated, reliable five-point Likert-scale questionnaire and analyzed through multiple linear regression. The results show that participative leadership has a positive and significant partial effect on job satisfaction (t = 2.051; p = 0.044), work climate has a positive and significant partial effect with a considerably more dominant contribution (t = 8.296; p < 0.001), and both variables simultaneously affect job satisfaction significantly (F = 97.396; p < 0.001), jointly explaining 75.6% of its variance. This study extends Path-Goal Theory and Social Exchange Theory to a public, non-profit, IT-based work unit, and recommends that management prioritize strengthening work climate as the primary lever for improving job satisfaction.